2006
DOI: 10.1002/app.23803
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of sPS/montmorillonite nanocomposites

Abstract: ABSTRACT:The present work analyzed the possibility of obtaining and producing syndiotactic polystyrene (sPS)-based nanocomposites. The work first focused on possible technology to use for intercalation from solution and melt intercalation. Using a blend of sPS with atactic polystyrene (aPS) as the matrix was also considered. Thermal analysis techniques, such as differential scanning calorimetry (DSC) and thermogravimetry (TGA), were used to study the thermal properties and stability of the nanocomposites obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…[45,55] The existence [46] of a thin interface layer that tends to enhance the segmental dynamics of the polymer chains and to lower the T g has been also found.…”
Section: Phase Structurementioning
confidence: 99%
See 1 more Smart Citation
“…[45,55] The existence [46] of a thin interface layer that tends to enhance the segmental dynamics of the polymer chains and to lower the T g has been also found.…”
Section: Phase Structurementioning
confidence: 99%
“…Similar results have been observed in PNs based on polyamide 6 (PA6), [2] polyamide 66, [43] polyamide 12 [44] and polystyrene. [45] Wide controversy exists on the glass transition region of polymer/clay PNs. An increase in T g or the creation of a new T g at higher temperature (similar to a new rigid amorphous fraction) can be expected as the result of confinement effects, interactions between the polymer and the filler inorganic particles [46] and restricted segmental mobility in the vicinity of the organoclay, which retards the cooperative motions of the polymer chains.…”
Section: Phase Structurementioning
confidence: 99%
“…A comparison of the 1 H-NMR spectrum of a-ph-ch-sPS with the 1 H-NMR spectrum of VsPSM indicates that during the reaction the chemical shifts of vinyl methylene (g) and methine (h) protons appear at 5 Scheme 1 Synthetic route of the vinyl-terminated syndiotactic polystyrene multicentre macromonomer (VsPSM) and graft copolymerization of methyl methacrylate onto syndiotactic polystyrene.…”
Section: Resultsmentioning
confidence: 99%
“…Organic-inorganic hybrids based on layered inorganic compounds, such as clays and organic polymers, have been studied because of their exceptional properties, such as increased modulus, strength, reduced gas permeability and enhanced thermal stability. [1][2][3][4][5] The dispersion of the silicate layers in the polymer matrix is improved by replacing the metal cations in the clay (such as sodium MMT; Na + -MMT) with ions bearing an aliphatic chain to compatibilize the silicate. This compatibilization enhances the silicate's interaction with the polymer by enlarging the interlayer, and the compatibilized clay is known as an organoclay.…”
mentioning
confidence: 99%
“…Moreover, Lee et al 40 showed that the glass transition temperature of graphene nanocomposites was raised, and the corresponding coeffi cient of thermal expansion was reduced. Besided, Torre et al 41 showed the strong infl uence of the preparation route on the thermal properties of polystyrene (PS) nanocomposites. An appreciable reduction in the Tg was observed only for composites obtained from solution, whereas the composites obtained by melt intercalation showed Tg values approximately equal to that of neat polymer.…”
Section: Thermal Properties (Dsc)mentioning
confidence: 99%